2009
DOI: 10.1016/j.jalz.2009.05.665
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression meta‐analysis model in Alzheimer's disease

Abstract: Baseline ADAS-cog is a significant covariate affecting the rate of disease progression, and it describes or at least explains the different rates of deterioration evident in early or late stages of the disease. There was no significant impact of publication year in the model, suggesting that disease progression has not slowed in more recent trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 75 publications
7
134
1
2
Order By: Relevance
“…this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17). Furthermore, several recent studies have reported slower rates of placebo decline in ad patients than traditionally assumed by older models and clinical trials (12,(21)(22)(23); they have also shown that baseline adas-cog significantly affects the rate of ad progression (23,24).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of mentioning
confidence: 99%
See 1 more Smart Citation
“…this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17). Furthermore, several recent studies have reported slower rates of placebo decline in ad patients than traditionally assumed by older models and clinical trials (12,(21)(22)(23); they have also shown that baseline adas-cog significantly affects the rate of ad progression (23,24).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of mentioning
confidence: 99%
“…to account for this issue, an ongoing study to investigate the efficacy of souvenaid in ad with adas-cog as the primary outcome measure (s-cONNect; NtR1683) includes patients with more moderate cognitive dysfunction (mmse 14-24) than the original study (mmse [20][21][22][23][24][25][26]. certainly, in the current analysis when the subgroup of ad patients with 'high' adas-cog scores at baseline was analyzed using Rmm, the data showed that souvenaid provided beneficial effects compared with control for up to 24 weeks.…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of mentioning
confidence: 99%
“…3 yrs (Bhargava et al, 2006). Ito et al observed an average MMSE loss of 5.5 pts/yr in mild to moderate AD in a metaanalysis (Ito et al, 2010). Encouraging a discussion and attempt to reach a consensus on the term "rapid cognitive decline", a threshold of 3 or more MMSE pt loss per six months has been proposed (Schmidt et al, 2011;Soto et al, 2008).…”
Section: Definition and Epidemiology Of Rapidly Progressive Admentioning
confidence: 99%
“…Several factors such as genetic properties, environmental circumstances, cerebral atherosclerosis, cognitive reserve, medical and social support contribute to disease progression (Etiene et al, 1998 Ito et al, 2010(576) Marra et al, 2000 sex (male) Roselli et al, 2009 (162) The role of comorbidity is subject to controversy. Diseases of the cardiovascular system and diabetes mellitus are commonly accepted as AD disease risk modulators.…”
Section: Clinical Signs Symptoms and Comorbidity As Predictors Of Famentioning
confidence: 99%
See 1 more Smart Citation